2011
DOI: 10.4161/cbt.12.11.18134
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone delayed weight loss and anorexia while attenuating adipose depletion in mice with cancer cachexia

Abstract: Cachexia is characterized by severe weight loss, including adipose and muscle wasting, and occurs in a large percentage of cancer patients. Insulin resistance contributes to dysregulated metabolism in cachexia and occurs prior to weight loss in mice with colon-26 tumor-induced cachexia. Therefore, we hypothesized that the insulin sensitizer, rosiglitazone, would attenuate the loss of adipose and muscle to result in improved outcomes for mice with late-stage cachexia. Male CD2F1 mice were inoculated with colon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Tumor mass (1125 § 127 mg) was markedly lower than in our previous studies of late cachexia. 31,32 Compared to the No Tumor group, final tumor-free body weight and muscle mass in the Tumor group were each reduced 13% but were not different from the Pairfed group (Fig. 1B and C).…”
Section: Effects Of Colon-26 Carcinoma On Adipose and Muscle Tissues mentioning
confidence: 92%
See 1 more Smart Citation
“…Tumor mass (1125 § 127 mg) was markedly lower than in our previous studies of late cachexia. 31,32 Compared to the No Tumor group, final tumor-free body weight and muscle mass in the Tumor group were each reduced 13% but were not different from the Pairfed group (Fig. 1B and C).…”
Section: Effects Of Colon-26 Carcinoma On Adipose and Muscle Tissues mentioning
confidence: 92%
“…Because C-26 carcinoma may induce anorexia in mice, 31,32 we included a pair-fed group in our study to determine effects of tumor independent of food intake. Cumulative food intake in the Tumor group was significantly lower compared to the No Tumor group beginning on day 11 of the study (Fig.…”
Section: Effects Of Colon-26 Carcinoma On Adipose and Muscle Tissues mentioning
confidence: 99%
“…The role of insulin signaling in preventing cachexia is further stressed by experimental data showing that mice treated with insulin sensitizers (rosiglitazone) 39, 162 and patients treated with insulin ameliorate cachexia symptoms. 163 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, no effect on body weight gain was recoreded in the same experimental model using pioglitazone although higher pioglitazone dose (100 ppm in a diet) increased food intake and insignificantly periovarial fat weight too [52]. Asp et al [53] reported initial weight loss delay and adipose depletion attenuation in mice with cancer cachexia administered with ROS, which, however, did not persist, food intake eventually declined as well. It seems that ROS cannot prevent weight loss in cancer subjects (which is mostly mediated by inflammatory cytokines) regardless of changes in food intake.…”
Section: Discussionmentioning
confidence: 95%